Penyusunan Laporan PTK bagi Guru SMP Negeri 13 Pekalongan - Sayyidatul Karimah; Rini Utami; Erwan Kustriyono; Nurina Hidayah (Indonesian Journal of Community Services, 2022)
Kegiatan pengabdian kepada masayarakat ini bertujuan untuk memberikan pelatihan dan pendampingan dalam penyusunan laporan peneltian tindakan kelas (PTK). Peserta pelatihan ini merupakan guru di SMP Negeri 13 Pekalongan yang berjumlah 30 orang. Pelatihan dilakukan secara daring dan luring selama tiga kali pertemuan yang bertujuan menghasilkan laporan PTK sesuai permasalahan yang dihadapi oleh masing-masing guru. Hasil pelatihan menunjukan guru harus lebih meningkatkan pemahamannya terutama terkait mengidentifikasi permasalahan pembelajaran, menganalisis hasil PTK dan meningkatkan kesadaran dalam melaksanakan PTK.This community service activity aims to provide training and assistance in the preparation of classroom action research reports (CAR). The participants of this training are teachers at SMP Negeri 13 Pekalongan, totaling 30 people. The training was conducted online and offline for three meetings aimed at producing CAR reports according to the problems faced by each teacher. The results of the training show that teachers must further improve their understanding, especially regarding identifying learning problems, analyzing CAR results and increasing awareness in implementing Classroom Action Research.